Implementation of HIV/AIDS Prevention Law Among Adolescent In Increasing Youth Resilience (Study at Dinas Pengendalian Penduduk dan Keluarga Berencana, Bekasi) - Anggita Hayuningtyas, Salsabila; Musyahadah Rahmah, Alef; Afwa, Ulil (LPPM Universitas Harapan Bangsa, 2025)
In Bekasi City, HIV/AIDS cases are relatively high, and adolescents are said to be vulnerable to HIV/AIDS transmission. Hence, Dinas Pengendalian Penduduk dan Keluarga Berencana, Bekasi City, needs to carry out the prevention according to Bekasi Mayor Regulation Number 125 of 2021. This research aims to determine the implementation of the HIV/AIDS prevention law among adolescents in increasing youth resilience by Dinas Pengendalian Penduduk dan Keluarga Berencana, Bekasi City, and the factors that influence the implementation of it. This research is qualitative research with an empirical juridical approach and descriptive specifications. The research informants were 5 (five) people. Types and sources of data include primary data and secondary data. The results of the research show that the implementation of the law on preventing HIV/AIDS among adolescents has been implemented well as measured by 4 (four) parameters, namely setting targets for preventing HIV/AIDS among adolescents, establishing partnerships in preventing HIV/AIDS among adolescents, facilitating HIV/AIDS prevention among adolescents with partners and establish HIV/AIDS prevention activities. Factors that tend to influence the implementation of HIV/AIDS prevention law among adolescents in increasing youth resilience consist of supporting factors, which at least include regulations regarding HIV/AIDS prevention, the readiness of human resources to carry out activities, and the availability of adequate facilities, and inhibiting factors which at least include difficulty for partners to work together, psychological counselling services which are only available 1 (one) for all adolescents in Bekasi City and unequal funding.